SYSTEMS USING NON-CONVENTIONAL RENEWABLE ENERGY SOURCES - T. Bo‘tayev; S. Nabixonov (European Science Publishing, 2023)
The article outlines systems for the use of traditional renewable energy sources, their production and application areas, and the structural scheme of the system of providing the population with uninterrupted energy.
Keywords: Traditional renewable energy source, energy resources, lighting systems, electrical appliances, heating systems, household appliances, consumer.